SOCIAL MEDIA DEMOGRAPHICS IN JORDAN AND THE EFFECTS OF ONLINE TRUST ON BRANDING USING SOCIAL MEDIA PLATFORMS * - AL ZOUBI, MUNIF MOHAMMED (International Journal of Psychosocial Rehabilitation, 2021)
This research aims to find a better understanding of the demographics using social media in Jordan, it will try to provide businesses in Jordan with the better understanding of which demographics they should be targeting when using social media platforms for their online marketing. Furthermore, the research will attempt to give businesses a better understanding of the effects of gaining a consumers trust on their brands image on social media platforms. The study population was collected online using multiple social media platforms, there was 859 respondents. The answers collected were part of a larger questionnaire conducted by the author for the PhD thesis. Design/methodology/approach: a quantitative method is used to find the the demographics that are using social media in Jordan and the effects of online trust on their usage of social media